NILAI PENDIDIKAN AGAMA HINDU DALAM ACARA NYENUK PADA KARYA NYATUR NGENTEG LINGGIH PADUDUSAN ALIT TAWUR PANCA KELUD DI MERAJAN SENTANA PASEK TOH JIWA SAMUAN - Aryana, I Made Putra; Wulandari, Ida Ayu Gde; Ni Wayan Arini (Guna Widya: Jurnal Pendidikan Hindu, 2024)
This article aims to analyze the value of Hindu religious education in the implementation of the Nyenuk event held in Merajan, a resident of Pasek Toh Jiwa Samuan. How the series of works by Nyatur Ngenteg Linggih Padudusan Alit is running. What is the procession of the Nyenuk event in the work of Padudusan Alit. As well as exploring the value of Hindu religious education in the ongoing Nyenuk event. The method used to collect research data is observation, interviews and literature study. The series of works by nyatur ngenteg linggih mapadudusan alit tawur manca kelud consists of various series of ceremonies. One of the important ceremonies is the Nyenuk ceremony. Nyenuk means coming to see which is a symbol of the descent of the god Nawa Sanga to see the success of the yadnya ceremony. This ceremony looks like mepeed as the end of the offerings and worship before Hyang Widhi Wasa in His manifestation which descends in a series of nyineb when performing the great work of mamungkah and ngenteg linggih. Every Hindu religious event definitely contains Hindu religious educational values, the teachings of which need to be passed down from generation to generation. The series of nyenuk events are of course carried out in accordance with literary instructions and in accordance with the instructions of sulinggih who leads the nyenuk event. The Nyenuk event contains the educational values of tattwa, morals, acara and is based on Tri Hita Karana.